Design of Hemispherical End Magnetorheological Finishing Tool for Diamagnetic and Paramagnetic Materials and its Experimental Investigations - Kansal, Harsh (My University, 2017)
Magnetorheological nano-finishing tool is a new advance finishing tool which is used to finish the flat surfaces of non-ferromagnetic (diamagnetic and paramagnetic) and ferromagnetic workpiece at the nano-meter level. Magnetorheological polishing fluid is used as finishing medium in this process. There is high need of nano-finishing of diamagnetic materials and paramagnetic materials such as copper, aluminium, etc. in various industries. Having excellent property of being light weight, nano-finished aluminium has wide applications in aerospace and automobile industries. Some industries like laser, aerospace, dentistry and metal optics etc. widely use highly finished copper mirrors. As these are soft and chemically reactive material, its surface finishing at nano level is difficult task. To fulfill this need, a new magnetorheological technique for precise finishing of diamagnetic materials and paramagnetic materials has been developed. Permanent magnets have been used for design and fabrication of the new tool namely hemispherical end magnetorheological finishing (HEMRF) tool. The finishing tool along with magnetorheological polishing fluid and workpiece has been modelled as well as simulated in Maxwell Ansoft V13 (student version) software to analyse the magnetic flux density distribution in the working gap. Experimentation has been performed to examine the performance of newly developed finishing tool to finish the flat surface of aluminium and copper workpieces. Magnetorheological polishing fluid is filled in the working gap of 1.5 mm that contains the cutting edged abrasives which results in material removal from the workpiece surface forming micro chips. The detailed study of the finishing process using statistical design of experiments for nano-finishing of copper is conducted. The performance of finishing process has been evaluated with the identified significant process parameters. Modeling of surface roughness with the effect of magnetic normal force at different finishing cycles has been proposed for the newly developed finishing process. Surface characteristics of both polished and unpolished workpiece are analyzed with the atomic force microscopy (AFM) and scanning electron microscopy (SEM). The results obtained from finite element analysis and experimentation assures that the newly developed hemispherical end magnetorheological finishing process (HEMRF) is capable to nano-finish of diamagnetic materials such as copper alloy etc.
Keywords: Diamagnetic materials; Hemispherical; Modelling; Magnetorheological; Nanofinishing; Paramagnetic materials; Permanent magnets; Simulation; Surface roughness